Performatividad discursiva y espacio(s) social(s) liminar(s). Una propuesta de aproximación a las prácticas comunicativas de migrantes indígenas quechua-bolivianos en Buenos Aires (Argentina) - Dreidemie, Patricia (2008)
Through Anthropologist Linguistics and exploration, the article proposes aparticular approach to the communicative practices of indigenous Bolivian-Quechuamigrants that resides in Buenos Aires, Argentina. The guiding question is if and how,within the liminal space of cultural vulnerability, stigmatization and migration, thelinguistic and discursive formal shapes emerge as particular resources ofappropriation-ness, (re)signifying or fight to establish social places, territories orcommunal jurisdictions. The order of the essay is as follows: first, it references andreflects on its theoretical and methodological base-concepts; second, it exposesthe ethno-linguistic condition found during field work; third, it lists and classifiesdifferent speech forms identified as functional in the discursive community atsocialization; and, lastly, it offers an example with a brief analysis of a singing performancegathered in the field.